A Normative Argument Against Explosion. (3rd February 2017) - Pinder, Mark
Abstract : One strategy for defending paraconsistent logics involves raising 'normative arguments' against the inference rule explosion . Florian Steinberger systematically criticises a wide variety of formulations of such arguments. I argue that, for one such formulation, Steinberger's criticisms fail. I then sketch an argument, available to those who deny dialetheism, in defence of the formulation in question.